Mutation of serine/threonine protein kinase 36 (STK36) causes primary ciliary dyskinesia with a central pair defect. Issue 8 (15th June 2017) - Edelbusch, Christine; Cindrić, Sandra; Dougherty, Gerard W.; Loges, Niki T.; Olbrich, Heike; Rivlin, Joseph; Wallmeier, Julia; Pennekamp, Petra; Amirav, Israel; Omran, Heymut
Abstract : Homozygous loss‐of‐function mutation in STK36 in OI‐105 II1 causes CP abnormalities. A : Sequence chromatographs of STK36 exon 12 amplicons demonstrate a homozygous deletion of one base pair (c.1399delG) predicting a premature termination of translation (p.Glu467Argfs*13). B‐C : Immunofluorescence staining of respiratory epithelial cells of a heathy control and individual OI‐105 II1 demonstrate the absence of STK36 (red) throughout the entire length of the ciliary axoneme in individual OI‐105 II1. Scale bars represent 10 μm. D : Schematic of a ciliary cross section of a motile 9+2 cilium and scheme of human ciliary components with a probable localization of STK36 (red) between the RS and CP. E : EM analyses revealed abnormalities of the central pair apparatus in some ciliary cross sections in OI‐105 II1. Scale bars, 0.1 μm. Abstract: Primary ciliary dyskinesia (PCD) is a genetic condition of impaired ciliary beating, characterized by chronic infections of the upper and lower airways and progressive lung failure. Defects of the outer dynein arms are the most common cause of PCD. In about half of the affected individuals, PCD occurs with situs inversus (Kartagener syndrome). A minor PCD subgroup including defects of the radial spokes (RS) and central pair (CP) is hallmarked by the absence of laterality defects, subtle beating abnormalities, and unequivocally apparent ultrastructural defects of the ciliary axoneme, making their diagnosis challenging. We identified homozygous loss‐of‐function mutations in STK36 in one PCD‐affected individual with situs solitus . Transmission electron microscopy analysis demonstrates that STK36 is required for cilia orientation in human respiratory epithelial cells, with a probable localization of STK36 between the RS and CP. STK36 screening can now be included for this rare and difficult to diagnose PCD subgroup.